(untitled) (International Research in Economics and Finance, 2022)
The development of artificial reproductive technology and the legal difference of surrogacy lead to a large number of transnational surrogacy children and many disputes about the legal parent status of transnational surrogacy children. The main reasons for the difficulty in identifying the parental relationship of the present transnational surrogacy children are the different identification of the surrogacy agreement and the parent-child relationship in different countries, the emergence of the "lame parental right" caused by the application of the principle of public order, and the reflect to recognize the transnational surrogacy parent-child relationship on the grounds of legal evasion. Based on the analysis of the reasons for the difficulty in identifying the parent-child relationship and the experience of determining the surrogate parent-child relationship in various countries, the exploration of the path to determine the parent-child relationship of the transnational surrogacy children mainly includes establishing the parent-child relationship according to the surrogacy agreement, establishing the adoption relationship to establish the parent-child relationship, and redefining the parent-child relationship according to the conflict norms of the country where the intended parents are located. At present, there is no basic law to regulate surrogacy in China. In practice, the legal parents of surrogacy children are established in the way of confirming the parentage of factual support. On the premise of balancing the best interests of children and social public order, we should protect the right of identity of transnational surrogacy children by perfecting laws and regulations, and maximize the function of technology to benefit mankind.